Kajian Ergonomi Meja Dan Kursi Pada Cafe Studi Kasus: Cafe Toko Kopi Kiri Kota Banda Aceh - Andrian; Eggy Fahrizy Manda; Zulfikar Taqiuddin (Jurnal Serambi Engineering, 2024)
Architectural design plays a crucial role in arranging the space and interior design of a cafe. The comfort of the facilities provided by the venue management is a key factor in determining the level of service satisfaction for visitors. Properly fulfilling the compatibility of facilities with user ergonomics will create a comfortable environment for activities in Lamteh District. In Ulee Kareng, Banda Aceh City, there is a cafe named Toko Kopi Kiri that serves food and drinks. The cafe is a popular spot for millennial residents of Banda Aceh City to stay in touch and socialize. However, the cafe's facilities are inadequate for long-term activities in terms of comfort, as observed in the field. This research uses qualitative methods to input data on the facilities and quantitative methods to process the data. The reference for this research employs literature studies on size standards. The research findings indicate that the facilities used at the Toko Kopi Kiri cafe do not meet ergonomic standards.